Correlation of Hand Grip Strength with Upper Limb Anthropometry of Bangladeshi Male Cricket Batsman (Bangladesh Journal of Anatomy, 2017)
Context: The estimation of hand grip strength is of immense importance in sports where a sufficient degree of power grip is necessary for success. In fact, many sports require a sustained level of hand prehensile force to maximize control and performance as well as reduce the possibility of injuries. The present study was undertaken to measure the correlation of hand grip strength with upper limb anthropometry of Bangladeshi male cricket batsman. The result may be used as a base-line for other professions as well for further research in our country. Materials & Methods: A cross sectional analytical type of study was conducted at department of Anatomy, Dhaka Medical College, Dhaka from July 2015 to June 2016 on fifty (50) adult Bangladeshi male sprinters (Group A) and fifty (50) adult Bangladeshi male cricket batsman (Group B). Sample collection was done by convenient purposive sampling technique. History of any injury of upper limb during playing was excluded to construct standard measurement. Total upper limb length was measured with the help of steel measuring tape. Hand grip strength Dynamometer was used to measure the hand grip strength. Results: The mean right and left hand grip strength was significantly higher (P